A MATLAB script and a methodology for the powertrain design of a fuel cells-battery hybrid electric supercar - Martino Diana; Lorenzo Martoccia; Stefano Fontanesi; Valerio Mangeruga; Alessandro d’Adamo (Energy Conversion and Management: X, 2024)
The urgency to decarbonize the transportation sector covers all kinds of vehicles, here included high-performance competition vehicles. Among the technologies able to guarantee zero emissions during the use phase, fuel cells (FCs) and energy storage systems (ESS), e.g. batteries, offer a great and still largely underexplored potential for complementary and synergic use in hybrid powertrains. Vehicles based on such technologies are cells-battery hybrid electric vehicles (FCHEV), and a niche of these are electric supercars (FCHES). In this context, the degrees of freedom of hybrid powertrains design and the different requirements of FCs and batteries frame the highly complex task of defining a clear and objective methodology to identify an optimal ratio among FC-battery power sources, whose lack jeopardizes a rigorous decision process as well as a general consensus and leads to the acceptance of sub-optimal solutions.In this study an energy/power-based methodology is developed in MATLAB environment considering the longitudinal vehicle dynamics of a typical high-performance parallel FCHES, using telemetry data from a real racetrack as common target for all the evaluated powertrain candidates and using realistic mass values. Under the constraint of equal performance (i.e., equal lap time), several FC-battery parallel hybrid powertrains are numerically evaluated with varying relative energy, power, weight, and under different regenerative braking levels. The set of obtained results allows to draw an objective rightsizing on the FC-battery power share and on the required energy capacity for a parallel FCHEV, as well as mass, hydrogen consumption, etc. The presented methodology offers a general use workflow applicable to any category of vehicles, supporting the engineering of hybrid FC-battery high-performance propulsion systems. The developed code will be made available upon request under the FAIR (Findable, Accessible, Interoperable, Reusable) guidelines.